Edukasi Pemanfaatan Nugget Jantung Pisang Kepok Terhadap Peningkatan Produksi ASI: Edukasi Pemanfaatan Nugget Jantung Pisang Kepok Terhadap Peningkatan Produksi ASI - Heryani, Sri; Mukti, Arifah Septiane; Rohmah, Siti (Ruang Ide Publisher, 2024)
Breastmilk (ASI) is the best source of food for babies, because breast milk has many contents that are very beneficial for babies. One of the benefits obtained is as an immune system in the body. So that achieving exclusive breastfeeding will reduce the infant mortality rate. Data from the World Health Organization (WHO) in 2020 stated that the rate of exclusive breastfeeding was 44% during the 2015-2020 period, this is also in line with a survey conducted by Lambantorium in 2018 which stated that the coverage of exclusive breastfeeding in Indonesia was still very minimal at 27 .6%. Efforts that can be made to increase the scope of breast milk production are by paying attention to the nutrition of breastfeeding mothers, where one effort that can be made is using plants to fulfill the nutrition of breastfeeding mothers. Plants that can be used are kapok banana blossoms. Where the Kepok banana flower is a type of plant that is easy to obtain, and the content contained in the Kapok banana flower is useful in increasing breast milk production. The aim of this service is expected to improve the status of successful coverage of exclusive breastfeeding and provide the latest study material regarding methods for increasing breast milk production.